Hyaluronidase-like enzymes are a frequent component of venoms from theraphosid spiders. (15th September 2017) - Rodríguez-Rios, Luis; Díaz-Peña, Luis Fernando; Lazcano-Pérez, Fernando; Arreguín-Espinosa, Roberto; Rojas-Molina, Alejandra; García-Arredondo, Alejandro
Abstract: Theraphosid spider venoms are extremely complex mixtures, composed mainly by low molecular compounds, peptides, and enzymes. The large size of these spiders and their ability to breed in captivity permits access to rather large amounts of venom and an easier venom extraction. In the present study, we conducted a comparative investigation about the content of hyaluronidase-like enzymes in the venoms from several theraphosid spiders, with a special focus on the Poecilotheria species, which are considered as underestimated theraphosids of medical importance. The following species were analyzed: Poecilotheria regalis, Poecilotheria ornata, Poecilotheria rufilata, Poecilotheria vittata, Bonnetina papalutlensis, Aphonopelma sp., Brachypelma smithi, Brachypelma epicureanum, Brachypelma boehmei, Grammostola porteri, Lasiodora klugi, Ceratogyrus darlingi, and Nhandu chromatus . The presence of hyaluronidase-like enzymes was evidenced in all venoms by a turbidimetric method and zymography. Several isoforms of acid-active hyaluronidase-like enzymes were detected in the venoms from Poecilotheria species. These results provide some biochemical characteristics of the high molecular mass proteins of the theraphosid venoms. Highlights: The presence of hyaluronidases was evidenced in all venoms analyzed. The venoms of Poecilotheria species contain acid-active hyaluronidase-like enzymes. The presence of several isoforms of hyaluronidase-like enzymes in Poecilotheria venoms was evidenced.